2007
DOI: 10.1097/nen.0b013e318126c179
|View full text |Cite
|
Sign up to set email alerts
|

Telepathology for Intraoperative Neuropathologic Consultations at an Academic Medical Center: A 5-Year Report

Abstract: Telepathology is an attractive solution for providing neuropathologic intraoperative expertise to geographically diverse hospitals from a center of excellence. To date, few reports specifically address the feasibility of such a system for intraoperative neuropathology specimens. The University of Pittsburgh Medical Center is a 20-hospital system in Southwest Pennsylvania in which the pathology department has adopted a subspecialty "centers of excellence" method of managing cases. The Division of Neuropathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 21 publications
4
37
0
Order By: Relevance
“…As such, it would not be appropriate to compare our performance with TP programs that have looked at resection margins, breast biopsy specimens, or lymph nodes. There are, however, 2 published reports on the use of TP for primary frozen section diagnosis in neuropathology that are very similar to our situation [7,14]. Hutarew et al [14] reported the use of RM for 343 frozen sections between 2002 and 2005 in Salzburg, Austria.…”
Section: Comparisons With Other Tp Frozen Section Programssupporting
confidence: 59%
See 4 more Smart Citations
“…As such, it would not be appropriate to compare our performance with TP programs that have looked at resection margins, breast biopsy specimens, or lymph nodes. There are, however, 2 published reports on the use of TP for primary frozen section diagnosis in neuropathology that are very similar to our situation [7,14]. Hutarew et al [14] reported the use of RM for 343 frozen sections between 2002 and 2005 in Salzburg, Austria.…”
Section: Comparisons With Other Tp Frozen Section Programssupporting
confidence: 59%
“…TP was viewed as a viable solution, and a solid business case could be made in support of its implementation. [14] 97.9 0 10.7 2007 Horbinski [7] 95.5-96.9 12-20 NA Abbreviation: NA indicates not available. a These reports did not provide deferral rates but rather the percentage of cases during which technical problems were encountered.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations